A taxonomic revision of the genus Anthriscus (Apiaceae) in Turkey - Teki̇n, Mehmet; Ci̇velek, Şemsetti̇n (Phytotaxa, 2017)
A taxonomic revision of Anthriscus (Apiaceae, tribe Scandiceae) in Turkey was carried out. The genus Anthriscus is represented by four sections and eight taxa, including six species with three non-typical infraspecific taxa in that territory, grouped into four sections: i) A. sect. Anthriscus (A. caucalis var. caucalis and A. tenerrima var. tenerrima); ii) A. sect. Cerefolium (A. cerefolium var. trichocarpa); iii) A. sect. Caroides (A. kotschyi); and iv) A. sect. Cacosciadium (A. lamprocarpa subsp. lamprocarpa, A. lamprocarpa subsp. chelikii, A. sylvestris subsp. sylvestris and A. sylvestris subsp. nemorosa). A new taxon, A. lamprocarpa subsp. chelikii, was found and published as a preliminary result of the present revisionary study. Some new characters such as length of filament and petal, and the ratio of fruit length to its beak length are used in the identification key for the first time. New localities of some taxa were found and their distribution areas are expanded. According to all morphological findings on Turkish Anthriscus, a new description of the genus was carried out. The taxonomic treatments for all taxa include type, synonyms (when present), morphological descriptions, phenology, and distribution areas (worldwide and local), habitats, phytogeographic region, conservation assessment and specimens examined. A new identification key for the sections and all Turkish species of the genus Anthriscus is reported, and illustrations and distribution maps in Turkey are also given for eight taxa.